Pengaruh Tata Kelola Perusahaan, Ukuran Perusahaan, dan Umur Perusahaan terhadap Manajemen Laba pada Perusahaan Minyak dan Gas yang Terdaftar di BEI - Manullang , Hilery Kislew; Soni, Okabrian (Jurnal Ilmiah Wahana Akuntansi, 2024)
The results this research show that partially, corporate governance and company size have a significant effect on earnings management. Company age has no direct impact and is not significant on earnings management. Corporate governance, company size and company age have a significant influence on earnings management. The results of the regression coefficient test show that earnings management is influenced by corporate governance, company size and company age by 34%. The existence of strict supervision, the impact of good governance, makes the opportunity for management to carry out profit management smaller. Large companies tend to increase their profits due to the competence and capabilities of the resources they have in managing the business. Younger companies want to show rapid growth and positive results to attract investors, while older companies have tighter oversight and more resources to ensure compliance with accounting standard.